Assessing the stock market torment of BRAC EPL Investment Limited in term of Revenue escalation - Zaman, Md. Mustafa (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.